2014
DOI: 10.1002/pssb.201451531
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of MBE‐grown asymmetric cubic GaN/AlxGa1–xN double quantum wells

Abstract: The non-resonant carrier transfer in asymmetric double quantum wells is studied. Asymmetric cubic GaN/Al x Ga 1Àx N double quantum wells with Al content of x ¼ 0.26 AE 0.03 were grown on 3C-SiC (001) substrate by radio-frequency plasmaassisted molecular beam epitaxy. The barrier thickness d between a wide quantum well having 2.5 nm thickness and a narrow quantum well with width of 0.7 nm was varied from 1 to 15 nm. Furthermore, high resolution X-ray diffraction reciprocal space maps around the (113) direction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Previous investigation on a similar ADQW structure with an Al content of 0.26 revealed coupling to start at 5 nm thick barriers. [24] For our samples the Al content is with 0.64 much higher, leading to a greater potential offset at the GaN/AlGaN interface. Thus the coupling starts for thinner barriers (below 3 nm).…”
Section: Discussionmentioning
confidence: 83%
“…Previous investigation on a similar ADQW structure with an Al content of 0.26 revealed coupling to start at 5 nm thick barriers. [24] For our samples the Al content is with 0.64 much higher, leading to a greater potential offset at the GaN/AlGaN interface. Thus the coupling starts for thinner barriers (below 3 nm).…”
Section: Discussionmentioning
confidence: 83%
“…The Burgers vector for a dislocation in a cubic zinc‐blende crystal, such as c‐GaN, is given by b=a/2, where a is the lattice parameter (). The lattice constant for c‐GaN is taken to be a=4.503thinmathspaceÅ . The calculated values for the dislocation densities are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The parameters used for nextnanoþþ can be looked up in Ref. [20] . Wecker et al have shown that the parameters they used fit very well for the calculation of the interband and intraband transitions of c-GaN quantum wells with nextnano3, so we expect comparably good results.…”
Section: Nextnanoþþ Simulationsmentioning
confidence: 99%